Censorship detected in EG (Egypt) - Voidly (Voidly Global Censorship Index, 2025)
CRITICAL severity censorship detected in Egypt. Data sourced from CensoredPlanet.
Censorship Incident ID: EG-2025-0002. Severity: critical. Confidence: 75%